Enhancing the Performance of Blue Quantum-Dot Light-Emitting Diodes Based on Mg-Doped ZnO as an Electron Transport Layer - Min-Ming Yan; Yi Li; Yong-Tian Zhou; Li Liu; Yong Zhang; Bao-Gui You; Yang Li (IEEE Photonics Journal, 2017)
Highly efficient blue quantum-dot light-emitting diodes (QD-LEDs) have been fabricated by substituting Mg-doped ZnO (MgxZn1-xO) for ZnO as an electron transporting layer (ETL). The device performance can be enhanced by optimizing Mg-doped ratios for the device structure of ITO/PEDOT:PSS/PVK/QDs/MgxZn1-xO/Al. The maximum luminescence efficiency and maximum brightness of blue QD-LEDs increase from 1.1 cd/A and 1500 cd/m2 for ZnO to 2.3 cd/A and 2500 cd/m2 for 10% Mg-doped ZnO (Mg0.10Zn0.90 O), respectively. The improved device performance should be attributed to balance electron and hole injection due to Mg-doped ZnO increasing the band gap and reduce exciton loss at the interface between the ETL and the emissive layer.